A visão de professores de ciências do ciclo II sobre o sistema de ciclos de formação e desenvolvimento humano da rede municipal de educação em Goiânia - AZEVEDO, Gislene Sousa de Sa (2009)
The aim of this study was to investigate the II cycle science s teacher s point of view about Ciclos de Formação (Formation Cycles) in the Teaching Municipal s Web in Goiânia. Since the role of teachers is to achieve any pedagogical proposal, it is important to identify what the teachers think about Ciclos de Formação (Formation Cycle) once they signified a very important change in the Teaching Municipal s Web in Goiânia. The research embraced all the formation II cycle s science s teachers of the Teaching Municipal s Web. The methodology used were the semi-organized interviews which had the purpose to comprehend and evaluate based on pedagogical aspects and the role of science teaching in this organization- the teachers about the implementation process of cycles in the Teaching Municipal s Web. The results of this work indicates that after eleven years of the Formation Cycles s implementation in Teaching Municipal s Web, there are, in the science s teacher s point of view progresses, equivocal, lack of comprehensions and great difficulties in the pedagogical conduction that shows the necessity to enlarge the study and to systematized the reflection about this teaching organization policy, their implications in the student daily classes and about the science teaching s role in the formation of the pupil. In this way, it is concluded that there are the necessity of offering, in the initial formation of science teachers, studying spaces and discussion about the nature of the scientific knowledge and the pedagogical politic aspects.